2017
DOI: 10.5812/jjm.12804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and In Vitro Antifungal Susceptibility of Candida Isolates from Women with Vulvovaginal Candidiasis in Northern Cities of Khuzestan Province, Iran

Abstract: Background: Vulvovaginal candidiasis (VVC) is a common infection, affecting up to 75% of women at least once during their lifetime. In addition, approximately 5% of patients may experience recurrent VVC. Candida albicans is the most common causative agent of VVC. Overall, precise identification of the causative agents of VVC is necessary for effective treatment. Objectives: The purpose of this study was to identify the molecular characteristics and antifungal susceptibility of Candida species, isolated from wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
4
19
2
Order By: Relevance
“…Despite C. glabrata is reported to be naturally resistant species to fluconazole or related azole antifungals [ 37 ], all the three vaginal isolates of C. glabrata in the current study were susceptible to fluconazole and other azole antifungals. Our finding is more or less concurrent with the findings of Hasanvand et al [ 34 ] in which out of 19 vaginal C. glabrata isolates only three isolates were resistant to fluconazole. Similarly, Richter et al [ 39 ] documented that out of 112 isolates of C. glabrata only 67% (51.8% susceptible- dose- dependent, 15.2% resistant) was fluconazole non-susceptible.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite C. glabrata is reported to be naturally resistant species to fluconazole or related azole antifungals [ 37 ], all the three vaginal isolates of C. glabrata in the current study were susceptible to fluconazole and other azole antifungals. Our finding is more or less concurrent with the findings of Hasanvand et al [ 34 ] in which out of 19 vaginal C. glabrata isolates only three isolates were resistant to fluconazole. Similarly, Richter et al [ 39 ] documented that out of 112 isolates of C. glabrata only 67% (51.8% susceptible- dose- dependent, 15.2% resistant) was fluconazole non-susceptible.…”
Section: Discussionsupporting
confidence: 92%
“…The study of Bauters et al [ 29 ] showed that C. glabrata as the most commonly isolated non -albicans Candida species (16.3%), followed by, C. parapsilosis (8.9%), C. humicola (1.6%), C. krusei (0.8%), and C. lusitaniae (0.8%). Hasanvand et al [ 34 ] demonstrated that C. albicans as the most commonly isolated species followed by C. glabrata, C. tropicalis , and C. parapsilosis. In contrast to these reports, C. krusei was the dominant non- albicans Candidia species in the present study accounting for 17.2% of the total isolates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, contrary to the notion that C. glabrata is intrinsically non-susceptible to fluconazole, all isolates in our study were sensitive to all azole drugs tested. More or less similar results were reported by many studies [17,27,43].…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the other studies in Iran [9,17,20], the lowest rate of dermatophyte species was isolated in the current study which can be due to the hygiene of the swimmers of our considered pools. In the present study, only one case of Trichophyton rubrum was isolated from foot-washing sink.…”
Section: Discussioncontrasting
confidence: 84%
“…Filamentous fungal isolates were identified by slide culture method [19]. Yeast fungal isolates were subcultured on CHROMagar™ Candida medium (CHROMagar, France) and incubated at 35°C for 48 h. Discrimination of Candida species and other yeast species was done according to different colors produced by Candida colonies in the chromogenic medium according to the manufacturer's protocol [20].…”
Section: Mycological Investigationsmentioning
confidence: 99%